Efektifitas Metode Team Assisted Individualization Dalam Pembelajaran Matematika di SD Dilihat Dari Self-Esteem Siswa - Yunita Wildaniati (MKKS SMA, MKKS SMP se-Kota Metro, Persatuan Sarjana Pendidikan Islam Wilayah Provinsi Lampung, dan CV.IQRO Penerbitan, 2020)
TAI learning model is a model that solves problems in individual teaching programs. In this model students are grouped based on diverse abilities. Research that is used to look for the effect of certain treatments on others under controlled conditions is called experimental research. The average value of students who have high Self Esteem taught using the TAI Method (75.7) is higher than those who are taught using the STAD Method (57.6). This means that the TAI Method is more effective than the STAD Method for teaching mathematics to students who have high self-esteem. The average value of students who have low Self Esteem taught using the STAD Method (64.8) is higher than those who are taught using the TAI Method (57.4). This means that teaching is more effective STAD method for teaching mathematics for students who have low Self Esteem.